PEMBERDAYAAN MASYARAKAT PENGUSAHA KECIL MELALUI DANA ZAKAT, INFAQ, DAN SEDEKAH (ZIS): Studi Kasus Program Masyarakat Mandiri Dompet Dhuafa terhadap Komunitas Pengrajin Tahu di Kampung Iwul, Kecamatan Parung, Kabupaten Bogor - Jaenal Effendi; Wirawan . (AL-MUZARA'AH, 2013)
Poverty is still one of big issues in the world particularly for developing contries. Poverty has close relation to the rural area where the people relied on agriculure activities for deriving income. Having a big Muslim population, Indonesia has great opportunity to utilize the huge potential of zakat fund particularly for empowerment program to the poor. Empowerment and capacity building program handled by Masyarakat Mandiri Dompet Dhuafa (MM-DD) to the poor people is believed to have a positive contribution to reduce poverty. The program includes providing business capital as agent of change and assistancy in order to increase the quality of human resources from the poor who generate income through producing tofu (in Kampung Iwul). Cross cultural innovation as well as regresion analysis is used to measure the program of MM-DD to their clients. The results show that based on the perception of the targeted clients regarding the indicator of material capabilties and intelectual, the empowerment program conducted by MM-DD reaches the goals of the program. While other perceptions linked to the manajemen ability from the targeted group show that the program can not reach the aims of MM-DD program yet. Several factors including their characteristics affected these perception. For the crosscultural innovation, most of respondent give positive response to the program. In addition, after adopting these programs, the avarage income of the people could increase. This increase is affected by the amount of lending, daily income from tofu business, and other income from other businesses.